Manajemen Pendidikan Anak Usia Dini Dalam Rangka Meningkatkan Mutu Pembelajaran Paud Bina Bangsa Islamic School - Rara Rasiana; Siti alikha allyasari (PUSTAKA: Jurnal Bahasa dan Pendidikan, 2023)
education is the right of every citizen, further to education at an early age that's the proper of citizens to extend their abilities from an early age. Early youth is a good basis in growing one's existence within the destiny. education given early on can optimize a baby's simple potential to accept instructional strategies at a more mature age. This observe goals to explain the mastery of early youth schooling in Bina Bangsa PAUD. This look at uses qualitative strategies and is descriptive in nature. The studies topics are college principals, educators, and college students. statistical collection is accomplished through remarks, interviews and documentation. The consequences of the observe show that the control of the Bina Bangsa PAUD software is built according with the imaginative and prescient and efforts of the business enterprise thru out- controlled abilties which encompass; making plans, imposing, monitoring and schooling. Managers as leaders in carrying out competency manipulation emphasize cooperation based totally on sincerity, enthusiasm and high loyalty. making plans is carried out through making strategic plans, compiling annual, semester, month to month, weekly to daily RPP.